Effect and safety analysis of auricular acupoint pressing therapy at different frequencies on insomnia and constipation (不同治疗频次耳穴压豆干预失眠和便秘的效果及安全性分析) - LIU Hongbo (刘泓博); JIN Xianglan (金香兰); SONG Jiale (宋佳乐); LI Jiaji (李佳霁); LIU Yanna (刘燕娜); WANG Xuesong (王雪送); GUO Jingrui (郭经睿); HU Shirong (胡世荣) (中西医结合护理)
Objective To investigate the effect and safety of auricular acupoint pressing therapy at different frequencies on insomnia and constipation. Methods Patients with insomnia and constipation who were hospitalized in the hospital from January 2023 to June 2024 were selected as the research objects. According to the random number table method, the patients were divided into the control group (continuous treatment of auricular acupointy pressing) (n=100), the observation group A (continuous treatment with auricular bean-pressing for 5 days, stopped for 2 days) (n=100), and the observation group B (continuous treatment with auricular acupoint pressing for 3 days, stopped for 1 day) (n=100). The patients with insomnia and constipation were intervened for 14 days, and the effect and safety of treatment were observed. Results After treatment, the total effective rate of treatment on insomnia and constipation in observation group A and observation group B was higher than that in control group (P < 0. 05). The Pittsburgh Sleep Quality Index (PSQI) score and Constipation scoring system (CSS) points of the three groups were improved compared with those before treatment (P < 0. 05). fter 14 days of treatment, the PSQI score and CSS scores of the observation group A and the observation group B were lower than those of the control group (P < 0. 05), and PSQI score and CSS scores in the observation group A were lower than those in the observation group B (P < 0. 05). The incidence of adhesive patch shedding and displacement in the observation group A and the observation group B were lower than those in the control group (P < 0. 05), and the incidence of adhesive patch falling off and displacement in the observation group A was lower than that in the observation group B (P < 0. 05). Conclusion The treatment frequency of auricular acupoint pressing for 5 consecutive days and stopped for 2 days is better in improving the symptoms of patients with insomnia and constipation, and reducing the risk of adhesive plaster falling off and displacement. (目的 探讨不同治疗频次耳穴压豆干预失眠和便秘的效果及安全性。方法 选取2023年1月—2024年6月医院住院治疗的失眠和便秘的患者为研究对象。应用随机数字表法将患者分为对照组(耳穴压豆每日连续治疗)(n=100)、观察A组(耳穴压豆连续治疗5 d, 暂停2 d)(n=100)、观察B组(耳穴压豆连续治疗3 d, 暂停1 d)(n=100)。三组耳穴压豆治疗方法相同, 但治疗频次不同。对失眠、便秘的患者进行干预14天, 观察治疗效果及安全性。结果 治疗后观察A组、观察B组失眠、便秘临床总有效率均高于对照组, 差异有统计学意义(P＜0. 05)。治疗后匹兹堡睡眠质量指数(PSQI)评分、慢性便秘严重度(CSS)评分三组较治疗前改善(P＜0. 05)。治疗14 d时观察A组、观察B组PSQI评分、CSS评分降低较对照组更明显(P＜0. 05), 且观察A组PSQI评分、CSS评分改善优于观察B组(P＜0. 05)。试验过程中观察A组及观察B组的胶贴脱落、移位发生率低于对照组(P＜0. 05), 观察A组胶贴脱落、移位发生率较观察B组低(P＜0. 05)。结论 采用耳穴压豆连续治疗5 d、暂停2 d的治疗频次, 对失眠、便秘患者症状改善效果更佳, 能够减少胶贴脱落、移位等情况发生。)